The Influence of the Computer Passion on the Development of Teens’ Reflection - Stril’chyk, Oksana (Psychological Prospects Journal, 2015)
In proposed publication there are results of research  held among 7th and 9th grade at Kyiv school with the risk of computer addiction and its relationship with the level of reflection development. The assumption in the research is that the high level of PC’s enthusiasm destructs the development of reflection  as  a mechanism  of  behavior  regulation.  The  empirical  research   covered48 students and consisted of two consecutive phases: measuring the level of computer’s enthusiasm and measuring of reflection’s level among interviewed students. The results of questionnaire demonstrated a high level of computer and Internet activity among the pupils. The most of the respondents in the  number  of  26 pointed that they play computer games often and very often. There were  only  six girls among this group of respondents. Besides the frequency of computer games playing, these pupils also demonstrated a high level of activity in the different kinds  of Internet practices like a long stay in the social Network, staying online during 4  and more hours a day. The analysis of the row of critically evaluated judgments  which were directed on the deeper diagnosis the problems related with the PC’s enthusiasm showed  that  the  most  interested  in  computer  and  Internet  pupils agree that they don’t notice as time passes when they  online,  that  they  have  a desire to reduce staying on computer, that they feel emotional exaltation before connect the network, that they have problems with their  study  at  school.  The  second part of research was directed on measuring of the level of the teen’s  reflection. The general amount of respondents was 35 persons (only 9th grade students). The method of the diagnosis of the reflection’s level by A.V. Karpov has been chosen as the key instrument. There was proved in the publication the reliability of the main assumption of the research through the visual demonstration  of  the  reverse feedback between the levels of the development of   the reflection and the frequency of computer games playing.
Keywords: risk of computer addiction, computer enthusiasm, reflection, social regulation of behavior